Microstructure and In Vitro Beta Carotene Bioaccessibility of Heat Processed Orange Fleshed Sweet Potato - Tumuhimbise, Gaston A.; Namutebi, Agnes; Muyonga, John H. (Plant foods for human nutrition, 2009)
Orange fleshed sweet potato (OFSP) has been identified as a good source of β-carotene but the β-carotene bio accessibility is affected by processing. In this study, the effect of traditional heat processing methods on the microstructure and in vitro bioaccessibility of β-carotene from OFSP were investigated. Bio accessibility was determined using simulated in vitro digestion model followed by membrane filtration to separate the micellar fraction containing bioaccessible β-carotene. Processing led to decrease in the amount of all-trans-β-carotene and increase in 13-cis-β- carotene. Processed OFSP had significantly higher (P<0.05) bioaccessible β-carotene compared to the raw forms. Bioaccessibility varied with processing treatments in the order; raw < baked < steamed/boiled < deep fried. Light microscopy showed that the microstructure of OFSP was disrupted by the processing methods employed. The cell walls of OFSP were sloughed by the traditional heat processing methods applied. The findings show that heat processing improves bioaccessibility of β-carotene in OFSP and this was probably due to
Keywords: β-carotene; Bioaccessibility; Orange fleshed sweet potatoes; Microstructure; Traditional heat processing methods